The value of urine specimens in screening for male urethritis and its microbial aetiologies in Tanzania. Issue 6 (December 1992) - Mayaud, P; Changalucha, J; Grosskurth, H; Ka-Gina, G; Rugemalila, J; Nduba, J; Newell, J; Hayes, R; Mabey, D
Abstract : OBJECTIVE--To evaluate the first void urine (FVU) specimen in screening for urethritis and its microbial aetiologies in a male African population in which urinary schistosomiasis is also prevalent. PATIENTS AND METHODS--Two hundred and forty eight males aged 15-54 years provided FVU specimens: 55 patients from a clinic for sexually transmitted diseases (STD), 151 patients from a medical outpatient clinic and 42 villagers from an area of high endemicity for S haematobium. Specimens were tested for leucocyte esterase (LE) using a dipstick (Nephur-Test+Leuco, Boehringer-Mannheim France SA). Ova of S haematobium were sought in terminal urine samples from all subjects. For all STD patients, and all medical outpatients with a positive LE test, urine and urethral swabs were tested for Chlamydia trachomatis antigen, and urethral swabs were tested for Neisseria gonorrhoeae by gram stain and isolation. RESULTS--The prevalence of LE positivity was 38/41 in STD patients with urethral signs or symptoms (93%), 5/14 among other STD patients (36%), 21/151 among medical outpatients (15%) and 13/42 among villagers (31%). As a screening test for urethral infection (detection of gonorrhoea or chlamydia and/or > or = 5 polymorphs per high power field on gram stain) the LE test had a sensitivity of 94% and a specificity of 53% among STD patients. Of 24 STD patients with gonococcal or chlamydial infection, 23 had a positive LE test (96%). Among general medical outpatients, 12 of 22 with a positive LE test had either conventionally defined urethritis or gonococcal or chlamydial infection, giving a positive predictive value of 55% for the LE test in this group. Of 18 subjects in all groups with urinary schistosomiasis nine had a positive LE test (50%), although three of these also had gonorrhoea. Chlamydial antigen was detected in the FVU specimen of all six subjects in whom it was detected in a urethral swab, and in an additional three subjects in the outpatient group. CONCLUSIONS--The FVU, which is an easily collected and non-invasive specimen, can provide valuable information on the prevalence of urethritis and on its microbial aetiology among the general male population in African countries.